(untitled) (Journal of Educational Sciences, 2017)
In this article thefeatures of the development of Turkish system of higher education areanalyzed, consideringmodern world and European integration processesstandards. The forms and methods of integration of the Turkish higher education in the Bologna process, an assessment of the prospects of development of the industry are highlighted. Is studied the part of the state in the management of higher education. The main characteristics and tasks of modern Turkish model of higher education are considered, as well as globalization, change of the technologies, the transition to the information technology society, the designation of sustainable development priorities and etc. The article discusses the complex ofcultural and educational institutions, public education component of the system, which contains a large educational system – the system of higher education. The stages of the reform of education, as this is a very topical and complex process, which is based on active, personal, system-structural approaches, are shown. Attention is focused on globalization trends, integration, humanization, continuity, differentiation, individualization, computerization,multilevelness, standardization, and the etc.